2020
DOI: 10.1111/jocd.13319
|View full text |Cite
|
Sign up to set email alerts
|

An experience of slow‐Mohs micrographic surgery for the treatment of Dermatofibrosarcoma protuberans: A long‐term cohort study

Abstract: Background Dermatofibrosarcoma protuberans (DFSP) is a rare dermal mesenchymal tumor known as a low‐grade, slow‐growing malignancy. The local invasion and high rate of recurrence following surgical treatment are the main concerns to plan the best surgical approach of treatment. Aims In the current study, it is aimed to provide an experience of slow‐Mohs surgery for the treatment of patients with DSFP. Patients/Methods Number of 25 patients with the diagnosis of DFSP through histological and immunostaining stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…On the paraffin section, a transition zone between tumor and normal tissue was easily identified; this zone was ill defined on the frozen section, even with immunohistochemistry CD34 staining, and normal skin showed scattered spindle dermal cells that could lead to confusion. Consequently, some authors suggested that slow MMS should be considered the optimal option for MMS 11,17‐22 . However, this statement was not supported by scientific evidence that confronted both techniques, until Lee et al 7 did.…”
Section: Resultsmentioning
confidence: 99%
“…On the paraffin section, a transition zone between tumor and normal tissue was easily identified; this zone was ill defined on the frozen section, even with immunohistochemistry CD34 staining, and normal skin showed scattered spindle dermal cells that could lead to confusion. Consequently, some authors suggested that slow MMS should be considered the optimal option for MMS 11,17‐22 . However, this statement was not supported by scientific evidence that confronted both techniques, until Lee et al 7 did.…”
Section: Resultsmentioning
confidence: 99%
“…Dermatofibrosarcoma Protuberans: Dermatofibrosarcoma protuberans (DFSP) is a low-grade, slow-growing cutaneous mesenchymal tumor with irregular borders and finger-like extensions into surrounding and deep tissues (Verma et al, 2020). DFSP often presents as an indurated plaque or nodule with minimal symptoms (Asilian et al, 2020). This tumor, as the most prevalent cutaneous sarcoma, accounts for 2% of all sarcomas, with an incidence of 0.8-4.2 cases per million persons annually (Lemm et al, 2009).…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 99%
“…40 They report the improved definition of paraffin sections allows for smaller margins with a median of 1.7 cm; however, the median time to receiving pathological results was 5 days (range 0-13) and 28% had to undergo more than 1 surgery. Asilian et al 41 recently published a review of 25 patients at a single center treated with slow-MMS with complete local control at 46.9 months and median margins of 1.9 cm. Although there are some benefits to slow-Mohs, it is more expensive, time-consuming, and may require patients to return for multiple surgeries, all of which limit the practicality of widespread use of this technique.…”
Section: Mms and Slow Mohsmentioning
confidence: 99%